2016
DOI: 10.1007/s00404-016-4177-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and risk factors of cesarean delivery with and without cesarean myomectomy in women with uterine myomatas

Abstract: CM performed by an experienced obstetrician can be safe in selected patients who are without additional preexisting risk factors. Risk factors that are associated with increased blood loss in women with uterine leiomyomatas include a larger size of the leiomyoma (≥5 cm) and a maternal age of ≥40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 14 publications
1
16
1
1
Order By: Relevance
“…Our data showed that the presence of a large-sized leiomyoma ≥5cm and birth weight ≥4,000 g were the important risk factors, while myomectomy during cesarean and the location and type of fibroids have little effects. In line with our study, Dedes I et al reported that a larger size of fibroid (≥5 cm) and a maternal age more than 40 years are risk factors of increased blood loss in women with uterine fibroids during cesarean [22]. Sei K et al investigated 759 pregnant women and reported the presence of a uterine fibroid of 175 cm 3 , birth weight of 2,500 g, and primipara were predictors for massive intraoperative hemorrhage during cesarean delivery [23].…”
Section: Discussionsupporting
confidence: 92%
“…Our data showed that the presence of a large-sized leiomyoma ≥5cm and birth weight ≥4,000 g were the important risk factors, while myomectomy during cesarean and the location and type of fibroids have little effects. In line with our study, Dedes I et al reported that a larger size of fibroid (≥5 cm) and a maternal age more than 40 years are risk factors of increased blood loss in women with uterine fibroids during cesarean [22]. Sei K et al investigated 759 pregnant women and reported the presence of a uterine fibroid of 175 cm 3 , birth weight of 2,500 g, and primipara were predictors for massive intraoperative hemorrhage during cesarean delivery [23].…”
Section: Discussionsupporting
confidence: 92%
“…In a retrospective cohort study by Dedes et al, 48 women underwent CM out of 162 pregnant women with myomas and rest had cesarean only (CO). 17 Overall there was no adverse outcome like hysterectomy or blood transfusion CM group. There was no significant difference in estimated blood loss (p=0.78), change in hemoglobin (p=0.60), operating time (p=0.13) or use of uterotonics (p=0.51).…”
Section: Resultsmentioning
confidence: 83%
“…4 Premature labor can occur in women who experience intractable pain and inflammation due to "red degeneration". 12,14,17 Obstetric concerns are considerably raised when myomas are complicated with secondary changes like necrosis, red degeneration (necrobiosis), torsion, impaction and hemorrhage leading to unbearable pain. Approximately 5-21% of women are hospitalized during pregnancy for pain control.…”
Section: Management Controversy and Complications Of Myomasmentioning
confidence: 99%
“…CM of multiple myomas, as well as those with pedunculated and subserosal myomas, was associated with both increased blood loss and surgical time compared to women with CS alone. There were no cases of hysterectomy or blood transfusions [11].…”
Section: Discussionmentioning
confidence: 94%